Efeitos preventivos do treinamento físico na expressão das proteínas Cox-2 e Vegf de ratos tratados com dexametasona - Dionísio, Evandro José [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Dexamethasone is a synthetic glucocorticoid widely used to treat allergic and inflammatory processes. This drug is used in three main situations, are used to contain acute or chronic inflammatory processes, or like immunosuppressive drug's. In these cases the patient will receive high doses for a chronic period and, therefore, has a much greater chance of adverse side effects, such as hypertension, diabetes and dyslipidemia. Dexamethasone promotes deleterious effects on the arachidonic acid pathway, when administered in high doses, because it is a potent anti-inflammatory drug. We recently demonstrated that dexamethasone significantly reduces the protein expression of vascular endothelial growth factor (VEGF) in both skeletal muscle and heart, but the mechanisms involved remain unclear. Meanwhile, exercise has been shown to be effective against high blood pressure, diabetes and dyslipidemia, promoting, among other factors, the increase in VEGF and angiogenesis. One possible explanation for these effects would be the creation of new vessels mediated by inflammation, or by the stimulation of the formation of products of the metabolism of arachidonic acid (AA), such as prostaglandin E2 (PGE2) and VEGF, by increasing the stimulation of the enzymes cyclooxygenase 1 and 2 (COX-1 and COX-2). Little is known about the preventive effects of training on the action of dexamethasone in the arachidonic acid pathway. Therefore, the aim of this study was to determine whether aerobic exercise training, performed before and concomitant treatment with dexamethasone, was able to prevent the effects of the dexamethasone in the protein expression of COX-2 and VEGF. For this, we used young Wistar rats (n = 40) which were randomly divided into 4 groups: sedentary control (SC), sedentary and treated with dexamethasone (SD), trained control (TC) and trained and treated with dexamethasone (TD). These rats performed aerobic exercise training, 60% of maximum capacity, 5

A dexametasona é um glicocorticóide sintético utilizada em três principais situações: para conter processos inflamatórios agudos, crônicos ou até como droga imunossupressora. Nestes casos o paciente receberá altas doses por um período crônico e, portanto, é muito maior a chance de ocorrência dos efeitos colaterais. Por ser um potente anti-inflamatório, a dexametasona tem promovido efeitos deletérios na via dos ácidos aracdônicos, quando administrada em altas doses. Demonstramos recentemente que reduz significativamente a expressão proteica do fator de crescimento de vasos derivado do endotélio (VEGF), tanto na musculatura esquelética quanto no coração, mas os mecanismos envolvidos neste efeito ainda não estão esclarecidos. Por outro lado, o exercício físico tem se mostrado eficaz no combate a hipertensão arterial, diabetes e dislipidemias, promovendo, entre outros fatores, o aumento de VEGF e da angiogênese. Uma possível explicação para essa criação de novos vasos seria pela via inflamatória, ou seja, por meio da estimulação da formação de produtos do metabolismo dos ácidos aracdônicos (AA), tais como prostaglandina E2 (PGE2) e VEGF, por meio do aumento da estimulação das enzimas cicloxigenase 1 e 2 (COX-1 e COX-2). Quase nada se sabe sobre os efeitos preventivos do treinamento físico sobre a ação da dexametasona na via dos ácidos aracdônicos. Portanto, o objetivo desse trabalho foi verificar se o treinamento físico aeróbio, realizado anteriormente e concomitantemente ao tratamento com dexametasona, foi capaz de prevenir e/ou atenuar os efeitos da droga na expressão das proteínas COX-2 e VEGF. Para isso, foram utilizados ratos jovens Wistar (n = 40) divididos aleatoriamente em 4 grupos: Sedentários controle (SC), Sedentários e tratados com dexametasona (SD), Treinados controle (TC) e Treinados e tratados com dexametasona (TD). Os mesmos realizaram treinamento físico aeróbio, a 60% da capacida
Keywords: Aptidão física; Glicocorticoides; Exercícios físicos; Musculos; Neovascularização; Educação fisica; Physical fitness